Life–Threatening Hyperkalemia Presenting with Cardiac Arrest during Combined Therapy with Angiotensin – Converting Enzyme Inhibitor and Spironolactone: a Case Report (Journal of Dhaka Medical College, 2021)
A 56-year-old man with history of previous coronary artery bypass graft (CABG) surgery and prior history of mild renal impairment was brought to the emergency department at mid night in gasping state. On presentation his pulse and blood pressure (BP) were non recordable. Cardiopulmonary resuscitation (CPR) was started immediately and he was intubated in the emergency room. Within few minutes his pulse became perceptible but BP still remained non recordable. His bed side 12 leads electrocardiogram (ECG) revealed sine wave configuration,suggestive of severe hyperkalemia with heart rate 30-35 beats per minute (bpm).Urgently he was transferred to cardiac catheterization laboratory for temporary pacemaker insertion (TPI). After putting TPI he regained consciousness and BP raised to normal. His blood gas analysis showed severe hyperkalemia (Serum potassium level-9.4 mmol/L). In coronary care unit (CCU) he was commenced on standard treatment of hyperkalemia and his electrolyte imbalance normalized within 24 hours. His cardiac rhythm reverted back to sinus within 24 hours of admission and he was extubated next day and discharged from the hospital after 5 days in a relatively stable state.J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 212-215